PERANCANGAN DAN IMPLEMENTASI AWAL APLIKASI FINEME BERBASIS FLUTTER UNTUK PENCATATAN KEUANGAN PRIBADI DIGITAL - Muhammad Midayatul Arifin; Salsa Nabila Harahap; Ruth Amelia Vega S.; M Yazid Noor; Adidtya Perdana (P3M STMIK Profesional Makassar, 2026)
Personal financial record keeping is often delayed or messy, making it difficult to summarize data, unconnected to budget limits, and easily overlooked. This research designed and built FineMe, a Flutter-based application for recording transactions, managing categories, setting total and per-category budgets, displaying daily charts, exporting data to CSV, and managing recurring transactions. The development followed a layered architecture software engineering approach with SQLite in the data layer, a repository for logic and aggregation, Riverpod for state synchronization, and a Material interface. Requirements were derived from daily usage scenarios and implemented iteratively, while functional testing assessed the accuracy of calculations and interface responsiveness. Results showed that the income, expense, and balance summaries were updated instantly, two separate daily charts were easy to read, budget progress was calculated accurately, valid CSV files were opened in a spreadsheet, and recurring transaction rules reduced repetitive input. These findings confirm the effective combination of Flutter, SQLite, and reactive state management for building a precise, responsive, and scalable financial recorder.